ANALISIS PERNIKAHAN USIA DINI DITINJAU DARI SUDUT PANDANG EKONOMI, SOSIAL DAN RELIGI : STUDI PADA KECAMATAN PURWODADI KABUPATEN GROBOGAN - Siti Fatimh Nurhayati; Indah Kurniasari (Universitas Muhammadiyah Surakarta, 2020)
This study is entitled “Analysis of Early Age Marriage From an Economic, Social and Religious Perspective: Study in Purwodadi District Grobogan Regency” with the aim of analyzing patterns of early marriage and factors that encourage early marriage. The research data uses primary data with a population of 103 and taken as many as 50 samples. Methods of data collection through observation, interviews, questionnaires and documentation. The analytical tool in this study uses descriptive qualitative analysis. The results showed that there were 2 reasons for early marriage, namely because of their own desires and arranged marriages. There are 3 patterns of early marriage, namely dispensation from the religious court, increasing the age of the KTP and siri marriage, and there are several factors driving the occurrence of early marriage which include economic factors, social factors and religious factors.